Cartazes nas margens: contestação, arte e produção do espaço - Fukushima, Kando (2019)
The present research aims at identifying and discussing the social mediations that occur in the context of the urban environment, particularly through posters that are distributed in noninstitutionalized spaces, in an irregular manner. In this regard, pictures taken from the central areas of Curitiba-PR and São Paulo-SP were analyzed, with the systematization of data related to aspects of production of these materials, their textual and visual language. The photographic records were made between January 2015 and September 2018 and were the basis to organize a collection of 500 images representative of the diversity of themes and visual approaches that are used in these prints. The examples analyzed are those that are related to social themes and poetic expression. It is considered the production of many social groups, artists and collectives, which interact and constitute the visual landscape of these cities. These materials are commonly ignored by the traditional history of graphic design or they are addressed only as manifestations that turn out to be public issues, such as those associated with visual pollution. In examining this production in more depth, it is pointed out the possibility of analyzing these artifacts in a context of economic, political and cultural exclusion, and as an autonomous and legitimate practice of contestation and appropriation of the city's space. The theoretical reference is guided mainly by the contributions of Henri Lefebvre, and his approach of daily life and the city, and Andrew Feenberg and the Critical Theory of Technology. Also discussed are the concepts that involve the posters within the field of design, highlighting some examples from the bibliography that were produced as a form of political contestation. The research points out the recurrent use of these graphic artifacts, and makes possible to recognize a great diversity of forms of expressing cultural and artistic identities and critical political stance. They represent a practice that is in constant tension with the regulations and highlight the urban space as a fundamental instance for social mobilization and political struggle.